2022
DOI: 10.1371/journal.pmed.1003979
|View full text |Cite|
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of SARS-CoV-2 vaccines in people living with HIV in the Netherlands: A nationwide prospective cohort study

Abstract: Background Vaccines can be less immunogenic in people living with HIV (PLWH), but for SARS-CoV-2 vaccinations this is unknown. In this study we set out to investigate, for the vaccines currently approved in the Netherlands, the immunogenicity and reactogenicity of SARS-CoV-2 vaccinations in PLWH. Methods and findings We conducted a prospective cohort study to examine the immunogenicity of BNT162b2, mRNA-1273, ChAdOx1-S, and Ad26.COV2.S vaccines in adult PLWH without prior COVID-19, and compared to HIV-negati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 35 publications
3
35
1
Order By: Relevance
“…As we hypothesized that this also holds true for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines, we previously investigated the immunogenicity of SARS-CoV-2 vaccinations in PWH with the vaccines currently approved in the Netherlands. Whereas smaller studies showed variable antibody responses after SARS-CoV-2 vaccination in PWH compared to HIV-negative controls [3][4][5][6][7][8][9], our study in 1154 PWH clearly demonstrated a diminished antibody response [10]. In total, 165 (14%) of the participants had a hyporesponse (≤300 spike [S]-specific binding antibody units [BAU]/mL by chemiluminescence immunoassay [DiaSorin Liaison]) and in 33 (3%) of them the antibody level remained below the cutoff level of test positivity (<33.8 BAU/mL).…”
contrasting
confidence: 71%
“…As we hypothesized that this also holds true for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines, we previously investigated the immunogenicity of SARS-CoV-2 vaccinations in PWH with the vaccines currently approved in the Netherlands. Whereas smaller studies showed variable antibody responses after SARS-CoV-2 vaccination in PWH compared to HIV-negative controls [3][4][5][6][7][8][9], our study in 1154 PWH clearly demonstrated a diminished antibody response [10]. In total, 165 (14%) of the participants had a hyporesponse (≤300 spike [S]-specific binding antibody units [BAU]/mL by chemiluminescence immunoassay [DiaSorin Liaison]) and in 33 (3%) of them the antibody level remained below the cutoff level of test positivity (<33.8 BAU/mL).…”
contrasting
confidence: 71%
“…In terms of mRNA vaccines, both non-significant 60,61 and significant decreases in humoral responses have been reported in PLWH. [62][63][64][65] These differences may be due to the size of cohorts examined and the range of immune reconstitution in these PLWH. In contrast to previous work, [8][9][10]12 we have found no association between the CD4 T cell count and serological outcome, which could be due to insufficient power in this study to detect differences.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Similarly, we indeed observed a dramatic decrement >180 days after the second inactivated vaccine dose. In a longitudinal cohort, a significant decrement of NAb titers was identified 8 months after the second inactivated vaccine dose, 21 which was distinctly mitigated by the triple-dose immunization regimen. 22 Thus, there exists an urgent necessity for a booster vaccination to enhance protection, especially for most-at-risk populations.…”
Section: Risk Factors Associated With the Seropositivity Of Sars-cov-...mentioning
confidence: 99%